Burnout among Hong Kong Chinese architecture students: The paradoxical effect of Confucian conformity values - Jia, Andrea; Rowlinson, S.; Kvan, T.; Lingard, H.; Yip, B. (Routledge, 2009)
Burnout is a multidimensional indicator of people's psychological relationship with their job, the opposite end of which is engagement. Culture's impact on students' burnout is investigated by examining the burnout level of Hong Kong Chinese architecture students and its correlation with Confucian conformity values, the dominant societal cultural values in Confucian-Heritage-Cultures (CHC)1 society. Two hundred and ninety-four students enrolled in Bachelor and Master programmes in architecture from two Hong Kong universities participated in the study. The Chinese version of Maslach Burnout Inventory-Student Survey and a seven-item conformity scale taken from the Schwartz Value Survey were employed to measure burnout and conformity values. Conformity values were found to be positively correlated with the EX dimension of burnout, negatively correlated with the CY (doubt significance) and the IE dimension of burnout, and not correlated with the CY (lose interest) dimension of burnout. The paradoxical effect of conformity values suggests that burnout is more than an individual phenomenon. Rather, it is a systematic problem rooted in the inconsistencies between the social culture in which the individual students are immersed and the learning culture of the architectural schools to which students are trying to adapt. Without an understanding of the contextual inconsistency, the burnout dilemma seems to be certain. The organizers of the architecture curriculum are urged to take students' social cultural context into account and address cultural diversity in their programmes.